Shedding Light on the Shade: How Nurseries Protect Their Children from Ultraviolet Radiation - Fießler, Cornelia; Pfahlberg, Annette Bettina; Uter, Wolfgang; Gefeller, Olaf (International Journal of Environmental Research and Public Health, 2018)
Minimizing exposure to ultraviolet radiation (UVR) is strongly recommended as the most important primary prevention measure regarding skin cancer. The responsibility for adequate sun protection of young children lies with their parents and external caregivers. Since a high proportion of 3- to 6-year-old children in Germany attend nurseries, the practice of sun protection in this setting was assessed. A survey was conducted in 246 nurseries in southern Germany during spring and summer of 2014 and 2015. Shade coverage in the outdoor area of the nursery was assessed by study team members and UVR protective behavior of staff was assessed by an interview with the directors. On average, 52% of the entire outdoor area and 65% of the children's outdoor play area were covered by shade, with a significant difference between nurseries of different sizes, pointing to a better shade coverage in larger nurseries. The daily outdoor stay was not regularly scheduled before or after peak sun intensity hours around noon to avoid intense UVR exposure. General sun protection rules were present in the majority of the nurseries and addressed predominantly wearing sunhats and applying sunscreen. Our findings show that current sun protection recommendations for children are only partially met in nurseries and indicate a lower level of sun protection in small institutions. Especially, avoidance of excessive exposure to UVR around noon and the importance of shade provision over play structures needs to be emphasized in future information campaigns.
EVALuna2:35662